Scope of soil cement in runways construction in India - Wadhawan, S. K. (Defence Science Journal, 2014)
The subject of soil-cement has been dealt with at some length. Developments in other countries in runway construction embodying soil-cement are reviewed and an account of Heavy Duty Military airport having soil-cement runway is furnished. Soils of India have been examined to determine their suitability for cement stabilisation. It is proposed that a percentage water stability of 80should be a good criterion of suitability of a given soil. Salient features of soil-cement construction are presented here and large scale field trials prior to adopting construction of soil-cement runways in the near future have been recommended.